Engineering properties of lightweight masonry unit produced from waste expanded polystyrene (eps) and rice husk ash (rha) - Ling, Ing Hock (Universiti Malaysia Sarawak (UNIMAS), 2012)
The depletion of non-renewable resources has become an alarming issue nowadays. Many environmentalists and researchers have been investigating the use of waste materials as a renewable resource for use as raw materials in construction. This research reports on the potential use of waste rice husk ash (RHA) and expanded polystyrene (EPS) beads in producing lightweight concrete bricks. The RHA was used as a cementitious material since it is a lightweight reactive pozzolanic material. The mixes prepared were made of RHA of 5%, 10%, 15% and 20% as partial replacement for cement and with the same amounts of sand and EPSI The EPS was used as partial aggregate replacement in the mixes. Four types of curing conditions were employed in this study. These include water curing, air-dry, 3-day water curing and 7-day water curing. The engineering properties of the bricks were investigated. Among the properties studied were hardened density, dimension compliance, compressive strength, water absorption, sorptivity and thermal conductivity of the EPS RHA concrete bricks. Scanning electron microscopy (SEM) was also performed on the brick samples. The results showed that RIO with 10% RHA replacement was the optimum mix. It had an average 28-day air-dry density of 1745 kg/m3 which classifies it as lightweight. For the dimension compliance, all bricks were within the specified values according to MS 76: 1972. In terms of compressive strength, it was found that RIO not only gained the highest compressive strength as compared to other samples but also complied with the Class 2 (14 N/mm2) requirement for load bearing bricks at 28 days as specified in Malaysia Standard. The water absorption, sorptivity and thermal conductivity for RIO at 28 days cured under different curing conditions ranged from 13% to 16%, 0.1 x 10-3 g/mm2/miri '5 to 0.142x 10-3 g/mm2/min°'5 and 0.36 W/mK to 0.468 W/mK respectively. In addition, it was observed that there was a thermal conductivity reduction of approximately 31 % as compared to control mix at 28 days which shows a significant amount of energy saving. The SEM analysis also showed denser microstructure arrangement for the RIO. It was found that the properties of the bricks are mainly influenced by the percentage of RHA replacement in the mix and also the curing condition used. The compressive strength of the EPS-RHA concrete brick increased with the increase percentage of RHA replacement in the mix. RIO with 10% RHA replacement (optimum mix) produced the highest compressive strength. The compressive strength decreased as the percentage of RHA replacement exceeds 10%. The water absorption and sorptivity values were decreased as the percentage of RHA replacement increased. The increase in RHA replacement produced lower thermal conductivity values. In general, full water curing is the most effective method of curing. It produced the highest level of compressive strength and thermal conductivity but the lowest value of water absorption and sorptivity.